O círculo operário católico em Sergipe : práticas educativas e organização da cultura operária (1935-1969). - Santos, Gilvan Vitor dos (2011)
This dissertation intends to analyze educational practices and the organization of working class culture, with emphasis on educational and cultural circle of the Catholic Worker of Sergipe, in the period 1935 to 1969. The Circle of Sergipe Catholic Worker is part of the process of romanization developed from the year 1910 in the diocese of Aracaju that will be reflected in the middle was proletarian in 1935. The study includes the experience of training Catholic worker, construction worker of the Catholic model. Aiming to show how did the experience of Catholic education in Sergipe proletariat from the role of the Catholic Worker Circle of Sergipe, using several sources: institutional and official documents, photographs, papers and studies related to the theme. For this, we used the categories of analysis of Norbert Elias - civilization; Roger Chartieu representations, among others. We seek to understand the political and social participation of workers under the auspices of the Catholic Church which stood in opposition to communism as a form of political awakening towards the organization of workers in Sergipe, since this action of the Catholic Church, in the middle proletarian Sergipe consolidates a new form of social participation, where Catholics and communists started fighting separately to organize workers in unions or associations.